The Group for Debates in Anthropological Theory (GDAT), The University of Manchester: The 2011 annual debate – Non-dualism is philosophy not ethnography. (September 2013) - Venkatesan, Soumhya; Martin, Keir; Scott, Michael W; Pinney, Christopher; Ssorin-Chaikov, Nikolai; Cook, Joanna; Strathern, Marilyn
Does the concept of non-dualism have ethnographic purchase or is it mainly of philosophical interest? This article comprises the edited presentation and discussions of the 2011 GDAT debate on the motion 'Non-dualism is Philosophy not Ethnography'. The debaters proposing the motion were Michael Scott and Nikolai Ssorin-Chaikov. They were opposed by Christopher Pinney and Joanna Cook. Marilyn Strathern acted as jester – playfully and rigorously engaging with all four speakers. The presentations and the discussions that followed were wide ranging, lively and stimulating.